Store Atmosphere, Product Quality, and Customer Satisfaction Toward Gen Z Loyalty at "Bersaudara Coffee" - Gevyma Tharis Iftikhor; Sri Tjondro Winarno; Taufik Setyadi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Coffee is one of Indonesia's most important commodities, providing income for coffee farmers, generating foreign exchange for the country, and serving as raw materials for industry. In recent years, the number of coffee shops in Mojokerto City has increased significantly, in line with growing public interest, especially among the younger generation, in coffee culture. This increase has sparked intense competition among coffee shops, prompting business owners to develop precise positioning and unique differentiation. Customer experience is now determined not only by the taste of the coffee but also by the shop's atmosphere and overall product quality. Toko Kopi Bersaudara in Mojokerto, as one of the local coffee shops targeting the Generation Z segment, needs to understand how these elements are interconnected. This study examines the impact of shop ambiance and product quality on customer loyalty, with customer satisfaction serving as a mediator. The study employs a quantitative approach using a survey method. Data collection was conducted in January and February 2025. Non-probability sampling techniques were employed, specifically a purposive sampling approach with elements of random sampling. With a sample of 100 respondents and WarpPLS 7.0 for data analysis, this study measured four variables: shop atmosphere and product quality (exogenous), customer satisfaction (mediation), and customer loyalty (endogenous). The model meets the criteria for both exogenous and endogenous models. The results indicate that store atmosphere and product quality have a positive and significant impact on Gen Z loyalty, mediated by customer satisfaction. To enhance satisfaction and loyalty, businesses can implement bundling strategies and membership reward programs. These findings provide practical insights and policy recommendations to improve Gen Z engagement and retention in small cafes like Bersaudara Coffee.